Impact of COVID-19 Pandemic on Teaching and Learning - Suneetha (International journal of economic perspectives, 2020)
The education in India was based on traditional way of learning where both teacher and the student were made to be present physically in a room and the teaching, learning process used to take at a scheduled time. The COVID-19 pandemic has created the largest disruption in the education systems in human history, affecting nearly 1.6 billion learners in more than 200 countries. Closures of schools, institutions and other learning spaces have impacted more than 94% of the world’s student population. This has brought a very drastic change in the teaching learning method. All the institutes switched from tradition way of learning to digital, mobile and online learning methods. Social distancing and restrictive movement policies have significantly disturbed traditional educational practices. Reopening of schools after relaxation of restriction is another challenge with many new standard operating procedures put in place.